2021
DOI: 10.1109/tbcas.2021.3110317
|View full text |Cite
|
Sign up to set email alerts
|

MBioTracker: Multimodal Self-Aware Bio-Monitoring Wearable System for Online Workload Detection

Abstract: Cognitive workload affects operators' performance principally in high-risk or time-demanding situations and when multitasking is required. An online cognitive workload monitoring system can provide valuable inputs to decision-making instances, such as the operator's state of mind and resulting performance. Therefore, it can allow potential adaptive support to the operator. This work presents a new design of a wearable embedded system for online cognitive workload monitoring. This new wearable system consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Several studies combine physiological signals with different machine-learning algorithms for CWM in different fields [13], [14]. However, to the best of our knowledge, we are the first to address CWM of drone pilots involved in SAR missions [8], [15], [16]. Now, we extend our previous works by presenting a subject-specific CWM approach based on noninvasive physiological signals that is suitable for new drone control solutions, such as FlyJacket [17].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Several studies combine physiological signals with different machine-learning algorithms for CWM in different fields [13], [14]. However, to the best of our knowledge, we are the first to address CWM of drone pilots involved in SAR missions [8], [15], [16]. Now, we extend our previous works by presenting a subject-specific CWM approach based on noninvasive physiological signals that is suitable for new drone control solutions, such as FlyJacket [17].…”
Section: Introductionmentioning
confidence: 76%
“…The first preprocessing step consists of removing the artifacts from the signals with causal filters [16]. We apply a baseline wander with cutoff frequency at 0.3 Hz to both ECG and PPG signals.…”
Section: B Signal Preprocessingmentioning
confidence: 99%
“…HR has also been used to detect stress levels, which exhibited correlation on subjects' stress state, regarding shortterm mental stress. It has been also used as a feature in a variety of studies addressing stress detection in humans [13,16]. In [16], a new design of a wearable embedded system for online cognitive workload monitoring is proposed.…”
Section: Human Monitoringmentioning
confidence: 99%
“…It has been also used as a feature in a variety of studies addressing stress detection in humans [13,16]. In [16], a new design of a wearable embedded system for online cognitive workload monitoring is proposed. Multiple signals are monitored (respiration (RSP), HR, skin temperature (ST) and pulse waveform) as a part of a multi-channel physiological signal acquisition and a low power processing platform.…”
Section: Human Monitoringmentioning
confidence: 99%
“…Results showed that HR can be an appropriate measurement for identifying a stress condition, as the transition from analog to digital induced stress. Finally, a study published recently, proposes a newly designed wearable system for online cognitive workload monitoring [12]. Multiple bio-signals (RSP, HR, ST and pulse waveform) were monitored during high and low cognitive workload, also focusing on a novel energy-aware algorithm for low-power processing.…”
Section: A Joint Human -Uav Monitoringmentioning
confidence: 99%